System and method for blending water. - Mohd Soom, Mohd Amin; Al-Jughaiman, Abdullah Sulaiman; Nisirat, Mahdi (2008)

(untitled)
The present technique relates to a method of blending water for producing biological water usage. The method includes identifying a salinity tolerance level for a plurality of crops using a database. In addition, the method includes estimating at least one volume of water relevant to an amount of crop yield of the plurality of crops using an algorithm. Furthermore, the method transfers at least one volume of water to balance the water salinity of at least one tank.